Conceptual Foundations for the Governance of Shared Solar Energy Resources - Hansen, Paula (Curtin University, 2020)
This thesis contributes to interdisciplinary energy studies by developing a set of propositions as conceptual foundations for the study and governance of sociotechnical shared renewable energy systems. It advances an understanding of how small-scale shared energy systems work to enhance their effectiveness and potential to support the low carbon transition